Respostas
respondido por:
1
Pa se dá por ax=a1+r , onde ax é o termo
a1 é o primeiro termo da pa, no caso 1
a2 = a1 + r = 1+2 = 3
a3=a1+2r=1+2.2=1+4=5
Ele te dá 3 termos, esses termos aumentam de 2 em 2 , logo, r=2
Com isso :
a13=a1+12r
a13=1+12.2
a13=1+24
a13=25
a1 é o primeiro termo da pa, no caso 1
a2 = a1 + r = 1+2 = 3
a3=a1+2r=1+2.2=1+4=5
Ele te dá 3 termos, esses termos aumentam de 2 em 2 , logo, r=2
Com isso :
a13=a1+12r
a13=1+12.2
a13=1+24
a13=25
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás